2022
DOI: 10.1093/brain/awab243
|View full text |Cite
|
Sign up to set email alerts
|

Broad activation of the Parkin pathway induces synaptic mitochondrial deficits in early tauopathy

Abstract: Mitochondrial defects are a hallmark of early pathophysiology in Alzheimer’s disease, with pathologically phosphorylated tau reported to induce mitochondrial toxicity. Mitophagy constitutes a key pathway in mitochondrial quality control by which damaged mitochondria are targeted for autophagy. However, few details are known regarding the intersection of mitophagy and pathologies in tauopathy. Here, by applying biochemical and cell biological approaches including time-lapse confocal imaging in li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 102 publications
6
23
0
Order By: Relevance
“…In the current study, we have provided more evidence to substantiate the role of altered motor-cargo interactions as a contributing factor to mitochondrial transport defects in P301L neurons. Consistent with the previous reports (Jeong et al, 2022), overexpression of P301L in mouse primary cortical neurons reduced anterograde movement of mitochondria, while having minimal effect on retrograde transport. Our data revealed that such defects are caused by reduced recruitment of kinesin motors to mitochondria in P301L cells.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the current study, we have provided more evidence to substantiate the role of altered motor-cargo interactions as a contributing factor to mitochondrial transport defects in P301L neurons. Consistent with the previous reports (Jeong et al, 2022), overexpression of P301L in mouse primary cortical neurons reduced anterograde movement of mitochondria, while having minimal effect on retrograde transport. Our data revealed that such defects are caused by reduced recruitment of kinesin motors to mitochondria in P301L cells.…”
Section: Discussionsupporting
confidence: 93%
“…As shown in Figures 1A,B, overexpression of wildtype tau did not affect either anterograde or retrograde transport of mitochondria. This is consistent with our previous work that control and wild-type tau expressing neurons display similar transport kinetics (Jeong et al, 2022). However, P301L tau selectively reduced anterograde mitochondrial transport but had minimal impact on retrograde transport in the same axon, ruling out the possibility of microtubule destabilization (Figure 1B).…”
Section: Tau P301l Inhibits Mitochondrial Transport In An Anterograde...supporting
confidence: 92%
See 2 more Smart Citations
“…Mitophagy is a critical mechanism in mitochondrial quality control that targets damaged mitochondria for autophagy. However, little is known about the relationship between mitophagy and pathologies in AD and other tauopathies (Jeong et al, 2022). The serine/threonine‐protein kinase (PINK1) and the E3 ubiquitin‐protein ligase (PARKIN) were recently involved in eliminating defective mitochondria by mitophagy (Cai & Jeong, 2020; Pradeepkiran et al, 2020; Sun et al, 2012).…”
Section: Introductionmentioning
confidence: 99%